Valoración del riesgo ambiental en la microcuenca Rumiyacu y su impacto ambiental en el distrito Moyobamba - Villarreal López, José Alejandro (2013)
The present investigation "ENVIRONMENTAL RISK ASSESSMENT IN THE MICROBASIN RUMIYACU AND ITS ENVIRONMENTAL IMPACT IN THE MOYO BAMBA DISTRICT" arises from the worrying and dizzying presence of dangers associated with conditions of vulnerability and the consequent risks generation. In this sense, it is vital that could generate altematives of planning, educational and of awareness with the local population in order to prevent the disasters from appearing of way appellant. The present report, seeks to determine the environmental risk assessment in the microbasin Rumiyacu through stages that are recommended to follow to ensure that a process of risk analysis will be completed successfully; al so to let them know that it is of the utmost importance is the manner in which the information collected in the field of participatory manner can be translated or decoded in cartographic information (maps) with the geospatial analysis techniques and propose a series of recommendations, so that the people who wish to implement the proposed methodology can adapt it according to their own characteristics. In the same way describes sorne concepts and methodology to assess the degree ofthreat or danger, vulnerability and risk. Under the premise that when it is a question of the environment is more valuable to be able to value that to have aptitude to repair, since the first thing determines deeply the second thing and even more, the environment is "really "irreparable", because of it the present investigation has a preventive purpose intrinsic, as one recounts lines above, while here developed allows to be contributed across recommendations not by concurrence of disasters that in the main are caused by the human activity.